A percepção dos trabalhadores da Rede de Atenção à Infância sobre a loucura em crianças: possíveis impasses para o objetivo de (re)inserção social proposto pelo atual modelo brasileiro de reforma psiquiátrica - Fabio Walace de Souza Dias (2012)
The present research has aimed at understanding the way the professionals related to the area of attention to childhood issues (schools, healthcare centers and Child Protective Service Councils) in the city of Santa Luzia, Minas Gerais, realize the psychic suffering in children, and if the ways of perception of such suffering would be restricted to some behavioral extent due to a preconcept about the child. We have inquired if the institutional discourses produced by these sectors, as well as the relationships established among them, could help the (re)production of instituted manners of seeing childhood, denying the psychic suffering in children, considering it as a mere deviating behavior to be brought back to normal state by a specialized healthcare service. When orienting these children to the correction of their behavior, would these sectors be denying the possibility of psychic suffering in them and also the possibility that they would present themselves to the world in a different way? Accordingly, we have investigated if the denial of insanity could constitute a possible obstruction to the fulfillment of the goal of (re)inserting users of mental health, as it is proposed by the Brazilian Psychiatric Reform, which aims at inserting them in the social environment as one of the possibilities of human experience. For that reason, the main methodological proceeding here was interviews with a group of professionals who work in the areas of health, education and defense of children and adolescents rights. The interviews have shown that the institutional discourses uttered about the child are based on an ideal of childhood that contributes to the construction of ways of being a child. The analysis of the discourses have also indicated a certain psychopathology attitude of child behaviors, denying the possibility of any child being considered as insane, when manifestations of suffering are delimited as a behavior problem to be corrected by the specialized service in mental health, named Centro de Atenção Psicossocial Infanto-juvenil (CAPSi).